Eight in one: morphological and molecular analyses reveal cryptic diversity in Amazonian alopoglossid lizards (Squamata: Gymnophthalmoidea). Issue 1 (2nd January 2020) - Ribeiro-Júnior, Marco Antonio; Choueri, Erik; Lobos, Simon; Venegas, Pablo; Torres-Carvajal, Omar; Werneck, Fernanda
Abstract: Among the currently recognized species of Alopoglossus, the Amazonian Alopoglossus angulatus has the widest distribution. We here analyse variation in scutellation and morphometrics of A. angulatus by examining 785 specimens of Alopoglossus . We also analyse intra- and interspecific genetic structure and differentiation using two mitochondrial ( Cytb and ND4 ) and two nuclear ( SNCAIP and PRLR ) genes from 97 samples. Both morphological and molecular analyses are based on specimens and samples from Brazil, Colombia, Ecuador, French Guiana, Guyana, Peru and Suriname. Our results reveal A. angulatus as a monophyletic group composed of eight independently evolved lineages: A. angulatus s.s. plus three revalidated species plus two newly described species plus two putative species. We provide descriptions of all taxa, except for the putative species, including the first description of the neotype of A. angulatus and redescriptions of resurrected junior synonyms. Illustrations, diagnoses and geographical distribution maps are provided. Gene and species trees are also provided. The two new taxa recognized in this paper, along with the revalidation of three taxa, increase the total number of known species of Alopoglossus from nine to 14.